Complete resolution of stage II avascular necrosis affecting three joints by hyperbaric oxygen in a patient with sickle cell disease: A case report - Alshurafa, Awni; Elhissi, Mohammad; Yassin, Mohamed A. (Frontiers in Medicine, 2022)
Avascular necrosis (AVN) or joint osteonecrosis is a debilitating complication of sickle cell disease, increasing the disease burden on both patients and health care systems. AVN can be radiologically categorized into early and late stages depending on the disease extent. Management of AVN is challenging and controversial. Generally, it includes conservative measures for early disease to preserve the joint for as long as possible and surgical management for more advanced diseases. Hyperbaric oxygen (HBO) therapy can be used as primary or adjunctive therapy for different medical disorders. Currently, HBO’s main rule in AVN is an adjunctive therapy to control symptoms and improve the quality of a patient’s life, however, the concept of using HBO as a primary treatment choice for AVN in sickle cell disease patients is not well evaluated yet. Herein, we report a 15-year-old male patient with sickle cell disease who was suffering from stage II avascular necrosis in bilateral femoral and right shoulder joints. 57 sessions of hyperbaric oxygen resulted in AVN complete resolution in post-treatment MRI.